(untitled) (Herald of Journalism, 2025)
In today’s media system, multimedia projects and longreads are widely recognized as innovative and integrated formats for delivering information. These formats are distinguished by their complex structure, multi-layered content, and the combination of various media tools (text, photos, videos, infographics, audio, etc.). However, current academic research and practical approaches still lack a unified theoretical framework and well-established concepts to define and analyze the notion of “longread.” This article explores the existing theoretical approaches and definitions that explain the nature of the longread format. It also highlights the merging of genres, methods, techniques, and formats in modern journalism, which leads to the emergence of new types of media products. Multimedia storytelling is inherently interactive, allowing audiences (users) to play an active role in determining the sequence and amount of content they engage with. The concept of "interactive multimedia narrative exposition" is applied as a method of structuring material in the longread format, especially when addressing socially significant topics. A longread does not merely convey information in a linear fashion; it encourages active engagement, emotional involvement, and personal experience from the reader. In this way, the longread is recognized as a syncretic media project situated at the intersection of traditional journalism and new media. This article analyzes the content and compositional structure of longreads, their relationship with media technologies, and audience perceptions of them. It also offers both theoretical and practical perspectives on the role of longreads in information dissemination, narrative style transformation, and contemporary media consumption culture. The aim of the article is to identify the relationship between multimedia tools and textual genres within the “longread” format. As a result of the study, multimedia longreads in new media and online versions of print publications are examined in detail. The scientific and practical significance of the article lies in identifying the structural, content-based, and multimedia features of the longread and demonstrating the relevance of this new genre in today’s media landscape from both theoretical and applied perspectives. The value of the research is in identifying the longread as a new multimedia genre in modern journalism.